SIMULTANEOUS DETERMINATION OF ATORVASTATIN AND ATENOLOL IN RABBIT PLASMA BY RP-HPLC METHOD AND ITS APPLICATION IN PHARMACOKINETIC STUDY - SHAH, SURAJ KUMAR; DEY, SANJAY; DE, SOURAV (International Journal of Current Pharmaceutical Research, 2022)
Objective: The objective of the present study is to establish a simple, sensitive, and specific RP-HPLC technique to determine atorvastatin calcium (ATV) and atenolol (ATL) in rabbit plasma. Methods: Both the drugs like atorvastatin calcium and atenolol have been extracted by simple liquid-liquid extraction with acetonitrile. Results: The chromatographic separation has performed on a reversed-phase C18 column with a mobile phase of phosphate buffer (pH 4.0): acetonitrile: methanol (40:40:20, v/v). The techniques have been validated over the concentration range of 22.08-4778.37 ng ml-1 for ATV and 18.35-3969.20 ng ml-1 for ATL in rabbit plasma. The acceptability range was satisfied for all validation criteria. These methods have been profitably applied to the pharmacokinetic study of a bilayer tablet of ATV and ATL after an oral administration to a rabbit. A significant recovery of the drug from plasma resulted from acetonitrile as extracting solvent compared to other organic solvents. Conclusion: The results obtained proved that the RP-HPLC method developed was accurate and reproducible, and the drug was stable in rabbit plasma.